Demometryczne modele umieralności ludności województwa katowickiego - Sojka, Elżbieta (Wydział Prawa i Administracji UAM, 1995)
The paper presents an attempt to build simple demometric models of mortality rates by sex, age and selected causes of death in Katowice province, a region ecologically endangered in Poland. Those models allow to analyse the sensitivity of the mortality process to changes in some of the factors related mainly to the pollution of the environment, urbanisation and industrialisation as well as broadly understood conditions of living and living standards. Mortality of men and women was presented in three group ages: pre-productive, productive and post-productive. In the model of causes of death, the following causes of mortality were analysed: cancer, circulatory system diseases and accidents, injuries and poisoning. Those three are commonly considered as civilisation illnesses causing in Katowice province 80% of all deaths.
Demometric mortality models shown by the population of Katowice province